2012
DOI: 10.1242/jcs.081703
|View full text |Cite
|
Sign up to set email alerts
|

NO/beta-catenin crosstalk modulates primitive streak formation prior to embryonic stem cell osteogenic differentiation

Abstract: SummaryNitric oxide (NO) has been shown to play a crucial role in bone formation in vivo. We sought to determine the temporal effect of NO on murine embryonic stem cells (ESCs) under culture conditions that promote osteogenesis. Expression profiles of NO pathway members and osteoblast-specific markers were analyzed using appropriate assays. We found that NO was supportive of osteogenesis specifically during an early phase of in vitro development (days 3-5). Furthermore, ESCs stably overexpressing the inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 87 publications
2
19
0
Order By: Relevance
“…These data coincide with a past study that showed improvement in proliferation of human osteoblast cells (CRL 1543) when the culture medium was supplemented with 0.0195% Tualang honey [30]. The underlying mechanism for the observed improvements is unknown, but it could be related to the active compounds present in Tualang honey or to the presence of H 2 O 2 , a ROS that is essential for modulating stem cell behaviours at the physiological level [45][47]. Pan et al (2011) recently suggested that low levels of H 2 O 2 (10–50 µM) could promote rabbit corneal epithelial cell attachment, mobility, and wound repair [48].…”
Section: Discussionsupporting
confidence: 89%
“…These data coincide with a past study that showed improvement in proliferation of human osteoblast cells (CRL 1543) when the culture medium was supplemented with 0.0195% Tualang honey [30]. The underlying mechanism for the observed improvements is unknown, but it could be related to the active compounds present in Tualang honey or to the presence of H 2 O 2 , a ROS that is essential for modulating stem cell behaviours at the physiological level [45][47]. Pan et al (2011) recently suggested that low levels of H 2 O 2 (10–50 µM) could promote rabbit corneal epithelial cell attachment, mobility, and wound repair [48].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our results, co-activation of NO, BMP2, and MAPK pathways are involved in osteoblast proliferation and differentiation downstream of phytoestrogeninduced osteogenesis [40]. NO is known to induce osteogenesis of ESCs through activation of canonical Wnt signaling [21]. More recently, our group has reported that Wnt signaling is associated with the osteogenic differentiation of stem cells under various experimental conditions [41][42][43].…”
Section: Discussionsupporting
confidence: 87%
“…A number of groups have demonstrated that NO encourages the differentiation of bone marrow-derived mesenchymal stem cells (MSCs) into osteoprogenitor cells [17][18][19]. However, whether NO is associated with the osteogenic differentiation of ESCs in vitro remains largely unknown [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, it has been shown that NO may act as a positive modulator of ␤-catenin activity under low basal Wnt activation. For instance, expression of iNOS (NOS2) in embryonic stem cells influences cell differentiation and early lineage commitment through activation of ␤-catenin (46). Another study showed that ␤-catenin associates with eNOS in quiescent ECs and that eNOS activation causes cGMP-dependent nuclear translocation of ␤-catenin and influences angiogenesis (47).…”
Section: Discussionmentioning
confidence: 99%